2018
DOI: 10.1063/1.5018335
|View full text |Cite
|
Sign up to set email alerts
|

Floating potential of emitting surfaces in plasmas with respect to the space potential

Abstract: The potential difference between a floating emitting surface and the plasma surrounding it has been described by several sheath models, including the space-charge-limited sheath, the electron sheath with high emission current, and the inverse sheath produced by charge-exchange ion trapping. Our measurements reveal that each of these models has its own regime of validity. We determine the potential of an emissive filament relative to the plasma potential, emphasizing variations in emitted current density and ne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…No simulation studies have analyzed how emission feedback cools plasma electrons. Experimental studies [5,18,19] have focused on measuring sheath properties, so the cooling of the plasma interior is not as well understood. Our new code is designed to study the cooling effect at a fundamental level.…”
mentioning
confidence: 99%
“…No simulation studies have analyzed how emission feedback cools plasma electrons. Experimental studies [5,18,19] have focused on measuring sheath properties, so the cooling of the plasma interior is not as well understood. Our new code is designed to study the cooling effect at a fundamental level.…”
mentioning
confidence: 99%
“…As it has recently become more and more obvious that in future large tokamaks such as ITER [80] the plasma heat flux onto Plasma Facing Components (PFC) can be as high 60 MW m −2 , a strong heating of the divertor plates up to white glow and consequent electron emission cannot be completely ruled out. This has renewed the interest in the interaction of plasmas with emissive walls [81][82][83] since, if the entire divertor becomes emissive, this will obviously have a drastic effect on the entire tokamak plasma.…”
Section: Electron Emissive Probes (Eep) 21 Basics Of Electron Emissive Probes (Eep)mentioning
confidence: 99%
“…Of course this derivation is simplified insofar as we have neglected the possible formation of space charges in front of an EEP [76,77,83,84]. Especially if there is a strong mismatch between the temperatures T em of the emitted electrons and of the plasma electrons T e , several experiments [33,34], theoretical [59,60,65] and numerical investigations [84] have indicated that the floating potential even of a very strongly emitting electrode in a plasma could always remain below Φ pl .…”
Section: Electron Emissive Probes (Eep) 21 Basics Of Electron Emissive Probes (Eep)mentioning
confidence: 99%
“…It was also recently demonstrated that an inverse sheath structure can appear near planar surfaces with electron emission yields exceeding unity and when collisions are important. [22][23][24] Again, orbital motion effects are not taken into account. Moreover, since a dust grain potential satisfies the floating condition, its electron emission yield remains below unity.…”
Section: Introductionmentioning
confidence: 99%